User Satisfaction and Challenges in Plavon Dukcapil Online Services - Rachmawati, Dyah Febri; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
General Background: The effectiveness of public administration services in Indonesia is crucial as the country transitions to digital platforms. Specific Background: This study examines the online services of Plavon Dukcapil in Rangkah Kidul Village, Sidoarjo Subdistrict, highlighting challenges faced by elderly users in navigating these services. Knowledge Gap: While existing research addresses the advantages of e-government, few studies focus on user satisfaction and effectiveness in rural areas, particularly regarding Plavon Dukcapil. Aims: This research aims to assess the effectiveness of Plavon Dukcapil's online services, focusing on community satisfaction related to service quality, speed, and accessibility. Results: Findings indicate that although service productivity aligns with regulations, efficiency is hindered by incomplete documentation and delays. Community satisfaction is compromised as many residents prefer in-person services over online options. Novelty: This study offers new insights into the operational challenges of e-government in rural Indonesia and highlights the need for improved community engagement. Implications: Enhancing communication and technical support for users, especially the elderly, could significantly improve the effectiveness and satisfaction of Plavon Dukcapil services, fostering better public service delivery in the digital era. Highlights: Digital Transformation: The study emphasizes the role of technology in enhancing public service accessibility and efficiency. Community Preferences: Many residents still prefer traditional in-person services over online platforms, indicating a gap in user experience. Need for Engagement: Improved communication and support for vulnerable populations, particularly the elderly, are essential for increasing online service effectiveness. Keywords: Plavon Dukcapil, Online Services, Community Satisfaction, E-Government, Public Administration